Simulation and Visualisation of Traditional Craft Actions - Xenophon Zabulis; Andriani Stamou; Ioanna Demeridou; Panagiotis Koutlemanis; Polykarpos Karamaounas; Vasileios Papageridis; Nikolaos Partarakis (Heritage)
Digital tools exhibit the potential to support the sustainability of traditional crafts through training and presentation applications. This work presents an integrated approach, combining state-of-the-art simulation and visualisation techniques to model mechanical actions characteristic of traditional crafts. This integration promotes a deeper understanding of the material behaviours and processes that are fundamental to traditional crafts, providing a valuable resource for researchers, educators, and conservators. Developed from an analysis of crafting activities regarding elementary actions, these tools support the safeguarding and education of craft techniques. The ability to realistically simulate and visualise crafting actions enhances applications in training and offers new avenues for the commercial presentation of craft products. The results demonstrate that this integrated approach yields detailed and realistic representations, providing a robust foundation for validating the traditional methods, comparing diverse techniques, and exploring innovative applications.